Innovations and Challenges in Modern Ambulance Services - Almass, Alhassan Hamad; Yaseen, Mana Mohammed; Al Mansour, Hussein Salem; Al Shaiban, Ali Salem; Al Saab, Salaiman Turki; Almansour, Ali Moeed; Zbid, Fahad Mohammad; Al Dwis, Nawaf Mana (Journal of medical and pharmaceutical sciences, 2024)
Objectives: This study investigates innovations and challenges in advancing ambulance services to ensure effective and safe out-of-hospital care, where patients may benefit from treatment at the scene or remain at home. This involves examining the integration of telemedicine, internet of things (IoT) connectivity, Artificial Intelligence )AI(, advanced life support, electronic patient records, and continuous vital sign monitoring to improve decision-making and emergency response. Methods: Through a comprehensive literature review, data was gathered on recent advancements in ambulance services. Key technological elements such as telemedicine applications, IoT-enabled devices, AI for emergency dispatching, mobile diagnostic tools, and electronic health records were analyzed. Emphasis was placed on how these technologies interact within the ambulance environment and the systemic challenges faced, including data security, interoperability, and infrastructure requirements. Results: Findings indicate that integrating these technologies can improve patient care by enabling real-time decision-making, reducing unnecessary transport, and providing access to remote medical expertise. However, issues such as data privacy, technological compatibility, and the need for robust internet connectivity remain significant barriers. Conclusions: Enhanced ambulance systems offer significant benefits for out-of-hospital care. Addressing operational challenges and implementing secure, interoperable solutions will be essential for realizing the full potential of these innovations, ultimately leading to more efficient and patient-centered emergency response.